Problems Faced by The Indonesian Medical Council in Determining Discipline Sanctions For The Medical Professional - Gisty Restu Widyajati; Juwita Juwita; Tiyar Cahya Kusuma (IHSA Institute, 2022)
Medical Practice is a series of activities carried out by Doctors and Dentists on patients in carrying out health efforts. During this practice, doctors and dentists did not escape disciplinary violations. If the patient / patient's family finds a doctor violating the doctor / dentist discipline, they have the right to submit a complaint to the Indonesian Medical Disciplinary Council. The complaint is an effort to protect the public from incompetent and non-standard medical practices. After the complaint is decided by MKDKI, MKDKI provides recommendations in the form of giving a written warning, revoking the Registration Certificate (STR) or Practice License (SIP) and / or the obligation to attend education or training at a medical or dental education institution to the Indonesian Medical Council (KKI). ) to be immediately stipulated in the form of a Decree of the KKI concerning Sanctions for Medical Professional Disciplines. Even though doctors / dentists have been given penalties in the form of disciplinary sanctions from the medical profession, there are still many doctors / dentists who continue to practice medicine even though the STR and SIP have been revoked / frozen. And do not carry out education or training as directed by MKDKI and KKI. The imposition of disciplinary sanctions for the medical profession is solely intended to create a deterrent effect on doctors / dentists and to improve professionalism as a doctor / dentist.